Specificity of Constructions Based on Combinations with Conjunction а and Concretizations posuti, posuchshestvu, vsuchshnosti - S. He (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The interaction between conjunction a and its concretizations po suti , po suchshestvu , v suchshnosti is examined. The research urgency is caused by necessity of comprehensive study of each function unit, expressing certain types of relations, the importance of identifying its constructive and co-occurrence possibilities. Practical implementation of the research of function vocabulary at the modern stage is seen in the possibility of a lexicographic representation of received information in special dictionaries. The paper provides a brief overview of the linguistic literature devoted to the description of lexemes po suti , po suchshestvu , v suchshnosti as lexicalized word forms and discursive words. The article focuses on the types of structures built on the basis of a combination of the conjunction a and mentioned concretizations. The novelty of the study lies in obtained results, not previously observed in works devoted to the studied conjunction and its concretizations. The analysis establishes that the conjunction a and mentioned concretizations have matching semantic elements, and that such a coincidence indicates the semantic coordination between the conjunction and its concretizations. The article shows the specificity of the structures with the conjunction a allowing to explicate adversative semantics of the lexemes po suti , po suchshestvu , v suchshnosti .